2018
DOI: 10.1108/mf-04-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Energy mutual funds and oil prices

Abstract: Purpose The purpose of this paper is to examine the price level and volatility impacts of oil prices on energy mutual funds (EMFs). The authors also examine specific fund characteristics which might influence those interactions. Design/methodology/approach The authors test for volatility transmission between the oil prices and the funds in the sample. Later, the authors test to see which fund characteristics impact these volatility interactions. Findings The results show oil price movements lead majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…For the comparatively less significant characteristics, we find the net vs. gross expense ratio, social risk score, and governance risk score to impact the probability of a price transmission at 5% statistical significance. Several studies have shown the importance of the Morningstar rating and manager tenure to be important in investor decisions (see Blake and Morey 2000;Ben-David et al 2022;Gormus et al 2018a;and others). Our tests provide further evidence of the importance of these "quality" characteristics in manager trading decisions and investor sentiment.…”
Section: Variablementioning
confidence: 99%
“…For the comparatively less significant characteristics, we find the net vs. gross expense ratio, social risk score, and governance risk score to impact the probability of a price transmission at 5% statistical significance. Several studies have shown the importance of the Morningstar rating and manager tenure to be important in investor decisions (see Blake and Morey 2000;Ben-David et al 2022;Gormus et al 2018a;and others). Our tests provide further evidence of the importance of these "quality" characteristics in manager trading decisions and investor sentiment.…”
Section: Variablementioning
confidence: 99%
“…Investors can benefit from the knowledge of fund managers and reduce costs through investing in energy mutual funds. Most energy mutual funds hold a substantial amount of stocks in various oil sectors, even though they diversify their holdings for alternative energy [32]. These fund managers prefer companies that operate within the oil industry for their sheer size and revenue.…”
Section: Oil Etf and Energy Mutual Fundmentioning
confidence: 99%
“…The rising oil prices increase the profits of the energy-producing firms. Gormus et al [32] identified a significant impact of crude oil prices on energy mutual funds. In particular, these authors also highlighted that energy mutual funds with better investment performance show higher interactions with the oil markets for both price and volatility [32].…”
Section: Crude Oil and Energy Fundmentioning
confidence: 99%
“…Several researchers found volatility transmissions between these markets in varying directions and with varying degrees of statistical significance (see Le and Chang 2015;Mensi et al 2017;Gormus et al 2014). Energy mutual funds heavily interact with the energy commodity markets (Gormus et al 2018(Gormus et al , 2023. Of particular interest when examining oil and gas focused mutual funds is how a firm deals with water issues.…”
Section: Introductionmentioning
confidence: 99%